THE FACULTY OF COUNTABLE SCIENCES OF THE NATIONAL MAJOR UNIVERSITY SAN MARCOS AGAINST THE CYBER-PLAGIARISM - Pastor Carrasco, Carlos Alberto (2009)
The present article intends to browse the abduction in general, in its pouring double: one for the fraudulent conversion and (against the author of the pirated work) another for the realized (regarding the addressees of the realized work with abduction) fraud. With these premises the academic defined ciber-plagio is analyzed as an abduction form carried out with the help of electronic available tools in the university environment. It is also sought: a) to Scan the nature of the online abduction; b) to Describe models to prevent the abduction; c) to Enter technology that can be used to identify the abduction; and d) to Scan actual forms of responding to the abduction, as well as the disciplinary treatment of the ciber-plagio with the regulatory scheme that they preparate the universities currently.